Mucosal Eosinophilia Is an Independent Predictor of Vedolizumab Efficacy in Inflammatory Bowel Diseases. Issue 8 (21st October 2019) - Kim, Erin M; Randall, Cara; Betancourt, Renee; Keene, Staci; Lilly, Amy; Fowler, Mark; Dellon, Evan S; Herfarth, Hans H
Abstract: Background: Peripheral and mucosal eosinophilia may be associated with more aggressive disease in inflammatory bowel disease (IBD) patients. Vedolizumab blocks T lymphocytes, eosinophil adhesion, and extravasation in the gastrointestinal tract. It is not known if mucosal eosinophilia is a predictor for the therapeutic efficacy of vedolizumab. Methods: This was a retrospective cohort study of IBD patients with ileal or colonic biopsies who were off steroids before starting vedolizumab. Biopsies were rereviewed by pathologists, and mean eosinophil density was quantified. Patient characteristics and steroid-free clinical response 6 months after beginning vedolizumab were determined. Features were compared between nonresponders and responders, and multivariable logistic regression was performed to identify predictors of clinical response. Results: Of 251 IBD patients starting vedolizumab therapy, 65 patients (48% Crohn's disease, 52% ulcerative colitis) met inclusion criteria. All IBD patients not responding to vedolizumab were more likely to have a higher baseline mean eosinophil count (340 ± 156 vs 236 ± 124; P = 0.004), be previously exposed to an anti-TNF (96% vs 56%; P = 0.001), and be male (58% vs 28%; P = 0.02). Mean eosinophil counts were significantly increased in colonic biopsies in UC nonresponders (438 ± 149 vs 299 ± 145; P = 0.01). A similar trend was seen in CD nonresponders. On multivariable analysis, colonic eosinophil density and prior anti-TNF exposure—and the combination of both—were independent predictors of response. Conclusion: In ulcerative colitis, colonic eosinophilia and prior anti-TNF exposure were independent predictors of 6-month clinical nonresponse to vedolizumab. Mucosal eosinophil density as a novel biomarker should be explored in larger patient cohorts. Aside from the previous anti-TNF exposure, eosinophil density in the colon of patients with UC is a negative predictor for a steroid-free long-term response to vedolizumab. The degree colonic eosinophilia may be a novel biomarker that should be further explored. Abstract : Aside from the previous anti-TNF exposure, eosinophil density in the colon of patients with UC is a negative predictor for a steroid-free long-term response to vedolizumab. The degree colonic eosinophilia may be a novel biomarker that should be further explored.